2020
DOI: 10.1016/j.ssmph.2020.100625
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal substance exposure, adverse childhood experiences and diagnosed mental and behavioral disorders – A longitudinal register-based matched cohort study in Finland

Abstract: Both prenatal substance exposure (PSE, alcohol/drugs) and experiences during the first years of life have powerful effects on brain development. However, only a few studies have investigated the combined effect of PSE and adverse childhood experiences (ACEs) on mental and behavioral disorders among exposed adolescents and adults. This longitudinal register-based cohort study 1) compared the nature and extent of diagnosed mental and behavioral disorders among youth with PSE and matched unexposed controls, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 58 publications
(103 reference statements)
1
15
0
Order By: Relevance
“…The negative association between offspring's mental and/or behavioural disorders and secondary education completion among both exposed and unexposed are supported by previous research indicating that mental and/or behavioural disorders can impair educational performance and be associated with inferior educational outcomes, due to difficulties with behaviour, self‐regulation, concentration, attention, and executive functioning and cognitive abilities (Brännlund et al, 2017; Howell et al, 2006; Jangmo et al, 2019; Polderman, Boomsma, Bartels, Verhulst, & Huizink, 2010). We have recently shown that childhood adversities and low birth weight are linked with offspring's mental and/or behavioural disorders (Koponen et al, 2020) similar to other studies (Aarnoudse‐Moens, Weisglas‐Kuperus, van Goudoever, & Oosteriaan, 2009; Björkenstam et al, 2017; Kambeitz, Klug, Greenmyer, Popova, & Burd, 2019). The results of the present study and prior research suggest then that the time lag in completed secondary education may not be a direct cause of prenatal substance exposure but rather reflect the impact of evolving offspring's mental and/or behavioural disorders influenced by adverse experiences during childhood.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The negative association between offspring's mental and/or behavioural disorders and secondary education completion among both exposed and unexposed are supported by previous research indicating that mental and/or behavioural disorders can impair educational performance and be associated with inferior educational outcomes, due to difficulties with behaviour, self‐regulation, concentration, attention, and executive functioning and cognitive abilities (Brännlund et al, 2017; Howell et al, 2006; Jangmo et al, 2019; Polderman, Boomsma, Bartels, Verhulst, & Huizink, 2010). We have recently shown that childhood adversities and low birth weight are linked with offspring's mental and/or behavioural disorders (Koponen et al, 2020) similar to other studies (Aarnoudse‐Moens, Weisglas‐Kuperus, van Goudoever, & Oosteriaan, 2009; Björkenstam et al, 2017; Kambeitz, Klug, Greenmyer, Popova, & Burd, 2019). The results of the present study and prior research suggest then that the time lag in completed secondary education may not be a direct cause of prenatal substance exposure but rather reflect the impact of evolving offspring's mental and/or behavioural disorders influenced by adverse experiences during childhood.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, the different domains of offspring's mental and/or behavioural disorders were more common among the exposed offspring compared with the unexposed. The common mental and/or behavioural disorders, deficits in neuropsychological functioning, in particular, and the association between prenatal substance exposure have been previously reported (Irner, 2012; Koponen et al, 2020 Sandtorv, Hysing, Rognlid, Nilsen, & Elgen, 2017). The negative association between offspring's mental and/or behavioural disorders and secondary education completion among both exposed and unexposed are supported by previous research indicating that mental and/or behavioural disorders can impair educational performance and be associated with inferior educational outcomes, due to difficulties with behaviour, self‐regulation, concentration, attention, and executive functioning and cognitive abilities (Brännlund et al, 2017; Howell et al, 2006; Jangmo et al, 2019; Polderman, Boomsma, Bartels, Verhulst, & Huizink, 2010).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…While an FASD diagnosis is associated with increased risk for the development of comorbid neurodevelopmental disorders, additional adverse childhood events further increased the rates of neurodevelopmental disorders in people born with FASD (Kambeitz et al, 2019). PAE alone does not sufficiently predict the rate of later disorders and youth with adverse childhood experiences, specifically out-of-home care, have the highest risk of mental health problems (Koponen et al, 2020). Additionally, children with PAE and subsequent postnatal adversity have different brain structures and symptom profiles than children without added postnatal adversity (Andre et al, 2020).…”
Section: Cumulative Impacts: Prenatal Alcohol Exposure (Pae) Followed By Early Life Stress (Els)mentioning
confidence: 99%
“…Although deficits in social cognition often underlie adult substance use disorders (SUDs) (Castellano et al, 2015; Sanvicente‐Vieira et al, 2017), little is known about the development of social cognition in the children of mothers with SUDs. Maternal prenatal SUD is accompanied by a variety of biological and psychosocial risks that may also predispose children to mental health and substance use problems (Koponen et al, 2020; Minnes et al, 2014). Deficits in social cognition are an important topic of study because they may precede the development of mental health and substance use problems.…”
Section: Introductionmentioning
confidence: 99%